Redefining tuberculosis: an interview with Lalita Ramakrishnan - Lalita Ramakrishnan (Disease Models & Mechanisms, 2023)
Professor Lalita Ramakrishnan is at the forefront of modern tuberculosis (TB) research. She has developed vital tools, most notably a robust zebrafish model, to study this disease, leading to seminal discoveries uncovering bacterial and host interactions throughout infection. Her group has harnessed this knowledge to develop new treatments for TB and shape clinical research. By unveiling these complex interactions, they have also improved our understanding of fundamental biology of macrophages and other infectious diseases, such as leprosy.